Behavior of an albino vampire bat, Desmodus rotundus (E. Geoffroy) (Chiroptera, Phyllostomidae), in captivity - Uieda,Wilson (2001)
Albinism in the common vampire bat Desmodus rotundus (E. Geoffrey, 1810) was already reported for seven individuals, six of them did in Brazil. Although this species is relatively easy to keep in captivity and many studies with normally pigmented bats were did under laboratory conditions, no reports on detailed observations of captive albino vampire bats were found in literature. This paper reports some behavioral observation of a single albino female D. rotundus kept in captivity in Brazil between 1991 and 1993. Information on feeding behavior, interactions with normally colored individuals and reproduction were recorded.